PENGARUH PROFITABILITAS, FINANCIAL LEVERAGE, DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM (Pada Sektor Consumer Good Industry Yang Terdapat di BEI Tahun 2017-2018) - Novita, Lela; Hakim, Mohamad Zulman (Jurnal Dinamika UMT, 2023)
Abstarct This study aims to examine the effect of profitability, financial leverage, net profit margin, current ratio, and return on aset on return saham. The dependent variable in this study is return saham. The population in this study are companies in cunsummer good sectors which were listed on the Indonesia Stock Exchange in 2017-2018. This study looks at financial statements issued by food and brevage during the study period. The method of determining the sample is done by using purposive sampling to ensure data obtained in accordance with the criteria in the study. From purposive sampling, 15 manufacturing companies were observed. The results of this study indicate that profitability and partial institutional ownership affect return saham, but net profit margin, financial leverage, current ratio, return on aset on return saham. While simultaneous net profit margin, financial leverage, current ratio, return on aset return saham.Key words:  profitability, financial leverage, net profit margin return saham